Dopaminergic neurodegeneration in Gerstmann–Sträussler–Scheinker (P102L) disease: insights from imaging and pathological examination - Irie, Ken-Ichi; Honda, Hiroyuki; Tateishi, Takahisa; Mori, Shinichiro; Yamamoto, Akifumi; Morimitsu, Makoto; Shinsuke, Kikuchi; Moritaka, Taiga; Kurata, Seiji; Kumazoe, Hiroyuki; Shijo, Masahiro; Sasagasako, Naokazu; et al. (Frontiers in Neurology, 2024)
Gerstmann-Sträussler-Scheinker (GSS) disease is an inherited prion disease characterized by dementia, cerebellar ataxia, and painful sensory disturbances. GSS is pathologically defined by the presence of amyloid plaques comprised of prion protein predominantly localized in the cerebral cortex, cerebellar cortex, and basal ganglia, resulting from mutations in the prion protein gene. This study investigated five cases of GSS P102L (GSS caused by a leucine (L) substitution of proline (P) at position 102 of the prion protein gene) with L-dopa-resistant extrapyramidal symptoms and reduced dopamine transporter single-photon emission computed tomography (DAT-SPECT) uptake. Clinical findings revealed diverse manifestations, with all cases exhibiting parkinsonism, and four patients had a vertical gaze palsy. Notably, all patients showed reduced striatal DAT-SPECT uptake, indicating neurodegeneration of the nigrostriatal system. Autopsy findings in one case confirmed prion protein plaques and dopaminergic neuron loss in the substantia nigra of a patient with GSS P102L. Additionally, reduced DAT immunostaining was observed in the putamen compared with a control. While previous studies have identified reduced DAT-SPECT and positron emission tomography uptake in Creutzfeldt-Jakob disease and fatal familial insomnia owing to nigrostriatal neurodegeneration induced by abnormal prion protein deposition, similar phenomena in 4 GSS P102L have not been reported. This study provides support for a correlation between abnormal prion protein deposition and nigrostriatal system degeneration in GSS P102L.Our results reveal the importance of considering GSS P102L in cases of atypical Parkinsonism and abnormal DAT-SPECT results, which would serve as a valuable indicator for subsequent prion genetic testing.